SDGs in the Business World: Do They Contribute to Financial Performance? - Paramitha, Diky; Etik Ipda Riyani; Raden Abdurrohman Thohir Wijaya (Terbuka Journal of Economics and Business, 2025)
Globally, many problems occur that concern the pillars of the SDGs. Research was conducted to find out whether there is an influence of SDGs performance with Environment, Health and Safety (EHS) indicators on financial performance measured through Return on Asset (ROA). The study sampled PT Astra Internasional data because the company regularly publishes sustainability reports and publishes them. Data processing used descriptive statistical testing using E-Views 13 with normality test, heteroscedacity test, autocorrelation test, multiple linear regression analysis, R Square test, F test, and t test. The results of the data analysis showed that the disclosure of the Environment, Health and Safety (EHS) sustainability report had no effect on the ROA of PT Astra International. Although PT Astra has fully disclosed its sustainability report to affect ROA, there are still other factors that fundamentally affect the Company's ROA level. This study has limitations in terms of the sample of companies because there are still companies that have not fully disclosed their sustainability reports, so this study uses a sample of one large company